Recent grassland losses are concentrated around U.S. ethanol refineries. (21st March 2017) - Wright, Christopher K; Larson, Ben; Lark, Tyler J; Gibbs, Holly K
Abstract: Although the United States has pursued rapid development of corn ethanol as a matter of national biofuel policy, relatively little is known about this policy's widespread impacts on agricultural land conversion surrounding ethanol refineries. This knowledge gap impedes policy makers' ability to identify and mitigate potentially negative environmental impacts of ethanol production. We assessed changes to the landscape during initial implementation of the Renewable Fuel Standard v2 (RFS2) from 2008 to 2012 and found nearly 4.2 million acres of arable non-cropland converted to crops within 100 miles of refinery locations, including 3.6 million acres of converted grassland. Aggregated across all ethanol refineries, the rate of grassland conversion to cropland increased linearly with proximity to a refinery location. Despite this widespread conversion of the landscape, recent cropland expansion could have made only modest contributions to mandated increases in conventional biofuel capacity required by RFS2. Collectively, these findings demonstrate a shortcoming in the existing 'aggregate compliance' method for enforcing land protections in the RFS2 and suggest an alternative monitoring mechanism would be needed to appropriately capture the scale of observed land use changes.